Ferroptosis‐related gene NOX4, CHAC1 and HIF1A are valid biomarkers for stomach adenocarcinoma. Issue 4 (13th January 2022) - Xiao, Ruoxi; Wang, Shasha; Guo, Jing; Liu, Shihai; Ding, Aiping; Wang, Gongjun; Li, Wenqian; Zhang, Yuqi; Bian, Xiaoqian; Zhao, Shufen; Qiu, Wensheng
Abstract: Ferroptosis is a regulated cell death nexus linking metabolism, redox biology and diseases including cancer. The aim of the present study was to identify a ferroptosis‐related gene prognostic signature for stomach adenocarcinoma (STAD) by systematic analysis of transcriptional profiles from The Cancer Genome Atlas (TCGA), GEO and a clinical cohort from our centre. We developed a predictive model based on three ferroptosis‐related genes ( CHAC1, NOX4 and HIF1A ), gene expression data and corresponding clinical outcomes were obtained from the TCGA database, and the reliability of this model was verified with GSE15459 and 51 queues in our centre. ROC curve showed better predictive ability using the risk score. Immune cell enrichment analysis demonstrated that the types of immune cells and their expression levels in the high‐risk group were significantly different from those in the low‐risk group. The experimental results confirmed that NOX4 was upregulated and CHAC1 was downregulated in the STAD tissues compared with the normal stomach mucosal tissues ( p  < 0.05). In sum, the ferroptosis‐related gene signature can accurately predict the outcomes of patients with STAD, providing valuable insights for personalized treatment. As the signature also has relevance to the immune characteristics, it may help improve the efficacy of personalized immunotherapy.